RECUPERACION DEL NITRÓGENO RESIDUAL DE LA PRODUCCIÓN DE LECHE - Amín, María Silvana; Degioanni, Américo J.; Bonadeo, Elena (European Scientific Journal, ESJ, 2014)
Bovine milk production generates effluents which, if they are not released, may be a source of environmental pollution. The use of this residue in plant production allows the capture of recidual elements in plants and soils without being transferred to the environment as pollutants, while improving yields and soil properties. The aim of this study was to evaluate the recovery of residual N from the effluent of milk production in maize. The experiment was conducted during two production cycles in a typical Haplustol in the province of Córdoba (Argentina). It had a complete randomized design with four witness treatments: witness plus three doses of effluent applications from 68,000 to 206,000 L ha-1. The effects on the crop (plants and yield achieved) and on the soil (organic and nitrate leaching) were evaluated. Apparent efficiency of nitrogen recovery was calculated. The results show that none of doses had an effects on the number of crop plants, soil organic matter and nitrate leaching. However, significant increases between 24 and 35% in corn grain yield were observed. Apparent N recovery efficiency varied between 1.55% to 19.33%. We conclude that, although the use of bovine milk production effluents in agricultural crops presents an apparent low N recovery efficiency, it is a viable technical alternative for increasing yields without transferring nitrogen to groundwater.